A Comparative Study of the Perspectives of Long‐Stay Immigrants, Nurses and Cultural Mediators on Intercultural Communication: A Secondary Qualitative Analysis - Francesc Ramos‐Roure; Maria Feijoo‐Cid; Josep Maria Manresa‐Dominguez; Jordi Segura‐Bernal; Rosa García‐Sierra; Maria Isabel Fernández‐Cano; Antonia Arreciado Marañón; Eduard Moreno‐Gabriel; Clara Flamarich Gol; Pere Toran‐Monserrat (Nursing Open)
ABSTRACT Aim To compare the perspective of nurses, long‐stay immigrants and cultural mediators on intercultural communication in care encounters. Design Qualitative secondary analysis of data obtained in two primary studies. Methods Two sets of data from two primary studies on nurses and long‐stay immigrants (including in total two focus groups and 15 in‐depth interviews) were merged. The sample was extended to include a focus group of cultural mediators. An amplified analysis was conducted using Charmaz's approach to grounded theory. Results The results are structured under the core category “Agreements and discrepancies in intercultural communication,” split into two subcategories: (1) Communication and the role of culture; (2) (Non) equitable and culturally (in)sensitive care. Immigrant patients and mediators detect barriers associated with generic aspects of communication, while nurses and mediators value culture. Nurses recognise paternalistic attitudes, while long‐stay immigrants sometimes detect biased treatment that mediators do not see. Immigrant patients and mediators value informal conversation as a strategy for cultural learning and building mutual trust, while nurses request regulated training. Conclusion The findings show that there are always discrepancies in this relationship. Changes to health care should be based on the participation of all actors. Communication skills training programs should be implemented. Implications for the Profession and/or Patient Care The convergences and divergences of nurses, immigrants and mediators expose new ways to approach care. Communication skills training programs should be implemented. Changes to health care should be based on the participation of all actors, including immigrant patients and mediators, and allow them to voice their opinions and make decisions. Impact This study addresses intercultural communication from three different perspectives: nurses, long‐stay immigrants and cultural mediators. Nurses, long‐stay immigrants and cultural mediators sometimes show convergence but never completely agree. The research may have an impact on primary‐care nursing by making it more culturally competent. Patient or Public Contribution Each participating long‐stay immigrant, nurse and cultural mediator reviewed their own interview. The findings were reviewed by a verifier member of each group (a nurse, patient and mediator).